IMPACT OF EDUCATIONAL REFORMS ON THE IMPROVING OF TEACHERS' TRAINING QUALITY IN THE NETHERLANDS - Anhelina Kolisnichenko (Pavlo Tychyna Uman State Pedagogical University, 2018)
This article analyses the state of education in the Netherlands during recent decades to define the main reforms which led to growth of Dutch's proficiency according to the European ratings. The rapid increasing of English speaking people in the Netherlands caused an interest to educational approaches which have pro-vided the high level of EL proficiency. The author shows positive role of connections between different stages of Dutch education, links between educational levels and employment. Much attention is given to the key components based on the formation of competencies necessary for successful professional realisation.  This article out-lines the peculiarities of secondary and higher education and the ways of teachers' training for different types of schools. The article presents definite interest to cultivating of the ability of new progressive teacher to respond to the recent challen-ges, which require the development of critical thinking and readiness to apply the innovative approaches which are relevant for democratic education. Selective approach of transferring between primary and secondary education is also described. The author points out the meaning of a binary Dutch higher education system for a distinction which is made between research oriented education in order to improve the level of training. It is emphasized a great diversity in Dutch education and the main drawback which can occur in teacher's training and the impact of university activity on quality of EL teachers training. The main steps which showed effective-ness in Dutch educational system defined in this article are as follows: consistent links between school stages, types of education and employment; support of common recommendations introduced by European Union countries; openness and free access to different resources; participation in European ratings; special attention to teachers' training, salaries, and courses for requalification. Positive Dutch experie-nce could be treated like preferable to follow for Ukrainian education.